A Study of Deep Ecological Crisis in D. H. Lawrence’s Poem "Love on the Farm" - Sharma, Bam Dev (Humanities and Social Sciences Journal, 2021)
This research article is based on the concept of harmonious interdependence between nature, living beings, and non-living beings for the sustained ecological balance. It makes an analysis of a poem by D.H. Lawrence, entitled “Love on the Farm” from deep ecological critical perspective. As a term, deep ecology explores how human beings, creatures, plants and trees are connected in the organic chain. Coined by Norwegian philosopher, named Aryan Naess, deep ecology became an assertive response to the menace of environmental crises taken place in different parts of the world. Considering its far-reaching consequences, universities and academic institutions began to study it seriously. As a result, initiatives were taken to broaden its study premise. Courses were devised and literary works were begun to be interpreted from ecological perspective and research outcomes produced significant insights and conclusions in order to explore this subject matter more comprehensively. On this backdrop, this article fundamentally sets three dominant premises for this research study: a) Human beings are sole causes for environmental loss, and, b) Ecological chain is prerequisite for the survival of the whole planet. On considering these premises, this present research article explores deep ecological elements in the poem “Love on the Farm” and how they are disturbed by domineering and more anthropocentric attitude of human beings. In proving the claim, this article takes first wave of eco criticism as a theoretical tool propounded by eco- critics like Jonathan Bate, Cheryll Gotfelty, and Lyn White, Jr. Then, it analyzes the poem, justifying how conflict with nature and ecology causes disturbance in entire environment. Finally, it concludes: ecological balance is the long-term solution to the survival of living and non-living beings as well as the longevity of whole planet.